Telepsychology in France Following the COVID-19 Crisis <subtitle>From Changes in Practice to Ethical Considerations</subtitle> - Lise Haddouk; Benoît Schneider; Tom Van Daele; Fredi Lang (European Journal of Psychology Open)
Abstract: Introduction: In cyberpsychology, telepsychology means providing psychological services using telecommunication technologies. Telepsychology has been increasingly implemented since the late 1990s. The Covid-19 crisis led to an acceleration in telepsychology practices, as evidenced by the major survey of psychologists’ online practices of the eHealth project group of the European Federation of Psychologists’ Associations (EFPA) in 2020. The crisis also allowed professional psychology organizations to frame telepsychology practices and disseminate existing recommendations more widely. Methods: This article aims to report on the specific situation in France, based on several sources of data: the original approach of the Fédération Française des Psychologues et de Psychologie to French psychologists; data provided by the EFPA’s e-health project group’s European survey; and data from a survey carried out in France. Results: The resulting analysis underlines the importance of ethical issues for the necessary regulation of practices. Discussion: The ethical dimensions of telepsychology call for sustained reflection about the professional framework of psychologists’ regulation in this evolving context. Conclusion: A discussion about the regulation of telepsychology is already going on in Europe, though it varies from country to country. The lack of training of psychologists in telepsychology remains to be addressed in the future.